Parental care and sibling competition independently increase phenotypic variation among burying beetle siblings - Schrader, Matthew (Evolution, 2018)
Several recent hypotheses suggest that parental care can influence the extent of phenotypic variation within populations; however, there have been few tests of these ideas. We exploited the facultative nature of posthatching parental care in the burying beetle, Nicrophorus vespilloides, to test whether parental care influences the expression of phenotypic variation in an important fitness trait (body size). We found that parental care and brood size (which influences sibling competition) had positive and independent effects on variation in body size. First, the mean coefficient of variation (CV) of body size was significantly greater in broods that received care than in those that did not. Second, CV body size increased with brood size in both parental care treatments. These results are not consistent with predictions from recent hypotheses that predict parental care will reduce phenotypic variation among siblings. The positive effects of parental care and brood size on phenotypic variation that we observed are likely due to sibling competition for access to provisioning parents and competition for limiting resources contained in the breeding carcass. Our results suggest that future theory linking parental care to the generation and maintenance of phenotypic variation must integrate the nature of interactions among family members.